2016
DOI: 10.1186/s12955-016-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-reported physical activity and health promotion behaviors on lung cancer survivorship

Abstract: BackgroundThere is some initial evidence that an enhanced physical activity level can improve fquality of life, and possibly survival among patients with lung cancer. The primary aim of this project was to evaluate the impact of physical activity on the quality and quantity of life of lung cancer survivors.MethodsBetween January 1, 1997, and December 31, 2009, a total of 1466 lung cancer survivors completed a questionnaire with patient-reported outcomes for quality of life (QOL), demographics, disease and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 39 publications
1
19
0
8
Order By: Relevance
“…39 Disease progression had a significant adverse impact on many PROs' endpoints; 40 PROs showed that they were useful in identifying patients with advanced NSCLC who are likely to have significantly lower survival. 41 The prognostic power of overall QoL on the survival of lung cancer patients and the advantages for lung cancer survivors reporting to be physically active was demonstrated versus those who were not physically active; 42 the early detection of symptomatic relapse and management of symptoms through a webmediated individualized follow-up strategy provided an improvement in quality of life and overall survival. 43 The third group included the studies that evaluated the agreement between the PROs and the evaluated parameters: concordance between LCSS and ECOG PS measurements and tumor-related symptoms is reported.…”
Section: Resultsmentioning
confidence: 99%
“…39 Disease progression had a significant adverse impact on many PROs' endpoints; 40 PROs showed that they were useful in identifying patients with advanced NSCLC who are likely to have significantly lower survival. 41 The prognostic power of overall QoL on the survival of lung cancer patients and the advantages for lung cancer survivors reporting to be physically active was demonstrated versus those who were not physically active; 42 the early detection of symptomatic relapse and management of symptoms through a webmediated individualized follow-up strategy provided an improvement in quality of life and overall survival. 43 The third group included the studies that evaluated the agreement between the PROs and the evaluated parameters: concordance between LCSS and ECOG PS measurements and tumor-related symptoms is reported.…”
Section: Resultsmentioning
confidence: 99%
“…Data from a prospective observational study in kidney cancer survivors investigating PA and diet changes suggested a decrease in the recurrence rate in patients who did any PA compared with those that were totally inactive [118]. The only study in lung cancer survivors showed better overall survival in patients who met > 9 MET-hours/week, but no difference in the recurrence rate was observed [119].…”
Section: Effect Of Physical Activity On the Prognosis Of Cancermentioning
confidence: 99%
“…In the setting of brain metastases, whole‐brain radiation therapy is also a predictor for development of impaired mobility [24]. Of note, patients receiving chemotherapy and/or radiation therapy self‐report less physical activity compared to long‐term lung cancer survivors and those who have recently undergone surgery [33]. It is unclear whether earlier detection of disease through the use of LDCT would obviate the need for chemoradiation therapy.…”
Section: Symptoms and Rehabilitation Needs Of Lung Cancer Patientsmentioning
confidence: 99%
“…Yang et al found that exercise improved HRQoL in 5‐year NSCLC survivors, despite the fact that symptom burden was not reduced [70]. In addition, self‐reported physical activity in lung cancer survivors improves physical, emotional, and mental well‐being, although it has no impact on disease recurrence [33].…”
Section: Survivorshipmentioning
confidence: 99%